Interference mitigation by power optimisation and frequency reuse technique on femtocell LTE network / Muhamad Fadhlan Md Ramli - Md Ramli, Muhamad Fadhlan (2016)
A femtocell is a tiny and low-power base station maximum power of transmission implemented in the building; commercial office or house which can be deployed via DSL connectivity. This femtocell network offers more adaptability and versatility for the deployment into existing structure. This will solve the problem of coverage at the cell edge of the macrocell coverage and also to the simplified concept of conventional LTE deployment. This report presents the analysis of interference mitigation method on femtocell in LTE network. Femtocell deployment required to providing better coverage for the user in the building. The simulation technique power measurement & frequency reuse using EXata Qualnet 5.3. The simulation results conclude the mitigation technique can reduce the interference and give better user experiences